Quantifying the interactive effect of water absorbing polymer (WAP)-soil texture on plant available water content and irrigation frequency - Saha, Abhisekh; Rattan, Bharat; Sekharan, Sreedeep; Manna, Uttam (Geoderma, 2020)
•Quantified interactive effect of water absorbing polymer (WAP) and soil texture.•Experimental reasoning for low improvement of WAP in fine textured soil.•Quantified the improvement factor for PAWC and plant survival time.•PAWC variation is minimal for clay content exceeding 30%.•Quantified optimum WAP application rate considering irrigation water requirement. Past decades have witnessed the impact of climate change resulting in extreme drought conditions, which necessitates innovative and sustainable approaches to enhance water use efficiency. Water absorbing polymers (WAP) are chemically cross-linked structures capable of absorbing and storing huge quantities of water within its three-dimensional network. Due to high water absorbency, these polymers are used for improving the water retention characteristics (WRC) of the soil during drought conditions. For this purpose, it is important to quantify the interactive effect of water absorbency of WAP and soil texture on water use efficiency. This study investigated the effect of WAP amendment on the drying water retention characteristic curve (WRCC) of three different textured soils. The study proved that the inter pore space of a fine-textured soil restricted the swelling of WAP to its full capacity. The combined WRCC and microstructural observations of bare and WAP amended soils added to the experimental reasoning for the comparatively low improvement in water absorption capacity (WAC) of fine-textured soil. At the maximum concentration of WAP application, the increase in plant available water content (PAWC) for coarse to fine-textured soil varied from 3.3 to 1.2 times, respectively. This study further demonstrated that the PAWC improvement factor is predominantly texture dependent and can be determined solely from the WRCC of a given soil. An empirical relationship was proposed for estimating PAWC and wilting time improvement factor based on particle size fraction of soil (texture). Based on the empirical models, it was concluded that the variation in wilting time and PAWC improvement factor was minimal for soils with clay content and fine content exceeding 30% and 60%, respectively. Based on the irrigation water requirement, the optimum WAP application rate for coarse-textured soils (sand, silt loam) was 0.1% while for fine-textured soil (clay loam) the application rate was 0.2%. The quantification presented in this study suggests the need to develop guidelines for WAP application by considering the soil texture to ensure optimal irrigation during drought condition.